B-Symbol Distance of Constacylic Codes of Length ps over Fpm + uFpm - H. Q. Dinh (2020)
© 2013 IEEE. In this research paper, the repeated-root constacyclic codes over the chain ring Fpm+ uFpm are considered, where p is a prime and m > 0 is any integer. The b-symbol distance for prime power length, i.e. ps is also studied for any integer s > 0. The Hamming and symbol-pair distances of all δ-constacyclic codes have been thoroughly studied in [18], where δ is an unit in the ring Fpm+ uFpm which is of the form ζ and φ + uφ, where 0 ≠ φ φ, ζ Fpm. In this paper, the b-symbol distance of all such δ-constacyclic codes of prime power length is computed for 1 ≤ b ≤ p/2. Furthermore, as an application, all MDS b-symbol constacyclic codes of length ps over Fpm+ uFpm are established.